The KNOWLEDGE OF POSTPARTUM MOTHERS AND HUSBAND'S SUPPORT ON POST-DELIVERY FITNESS - Junengsih junengsih; Shentya Fitriana; Jehanara Jehanara; Mukhidah Hanun (Jurnal Fisioterapi dan Kesehatan Indonesia, 2023)
Introduction: The puerperium or puerperium is the period that occurs immediately after giving birth. The postnatal period is a critical period, known as the recovery period, which begins when the placenta is born and ends when the reproductive organs return to their pre-pregnancy state. Pregnancy and childbirth have a great impact on physical fitness. Healthy individuals with uncomplicated pregnancies may experience a prolonged decline in physical fitness. Methods: This research was conducted with a quantitative approach. The research design used was cross sectional, with primary data and a sample of 80 postpartum mothers. The analysis used is chi square and multiple logistic regression. Results: The behavior of postpartum women at the Depok Jaya Inpatient Clinic showed more than half of postpartum fitness. However, this already illustrates that postpartum mothers already have good knowledge and behavior towards efforts to improve postpartum fitness which of course cannot be separated from the support of their husbands who are the closest people to postpartum mothers. Postpartum mothers who have good knowledge have a 3 times higher chance of having good behavior towards postpartum fitness than mothers who have less knowledge, but cannot be separated from their husband's support. Conclusion: Husband's knowledge and support are two things that cannot be separated that can affect postpartum fitness in postpartum women. Health workers, especially midwives in basic services such as TPMB or Puskesmas, need to involve their husbands in providing care during the postpartum period. Recommendations for basic level services such as TPMB or Puskesmas in providing services to postpartum mothers and conducting health education, especially physical health, psychological health should involve husbands to be directly involved in improving postpartum fitness